Informationsfrihet och IT-användning i demokratifrämjande syfte - Fältskog,Sara; Ihanus,Janica (2004)
The potential of information technology as a means to invigorate democratic practise is constantly under discussion. Regardless of the differing opinions as to the most suitable way to utilise IT, there are certain democratic core values that have to be considered. One of these is freedom of information, defined by us as the right of every citizen to seek, obtain and express information. The aim of this study is to explore whether the use of IT as a means to enhance democracy can strengthen the citizens right to freedom of information. As an instrument for analysis we use an article by Jan van Dijk, professor of communication science. Dijk discusses the relationship between six different models of democracy and fifteen particular applications of IT. Using the concept of communication patterns, which demonstrate whether the information is controlled by a central unit (e.g. a government or a political party) or by an individual (the citizen), he presents six examples of how IT can be used to enhance democracy. Using the article as a starting point, we examine whether the citizens right to seek, obtain and express information can be strengthened by the use of IT in each of the six models of democracy. We consider the motives that underlie a certain usage of IT as well as the communication patterns. We conclude that the use of IT can strengthen the right to freedom of information on condition that the citizens are provided with information from a variety of sources and that the applications of IT enable interactivity, thereby making it possible for the individual citizen to express information. This type of IT usage is preferred when the motivation is to increase and encourage citizen participation by creating more direct forms for participation and decision making, which is the case in four of the models of democracy examined. The IT applications favoured by the remaining two models are intended to improve the quality of existing institutional politics. The information is produced and transmitted by a central unit rather than by the individual citizen. It is not used as a means to enable communication and political discussion between citizens or between citizens and their representatives. Thus, the right to seek, obtain and express information is not strengthened.
Keywords: informationsteori; internetanvändning; Internet; Documentation, information, library science, archivistics; Arkiv- och bibliotekskunskap, dokumentation